Analysis of expression profile of long non-coding RNA in patients with idiopathic and COVID-19-induced pulmonary fibrosis - G. F. Korytina; I. A. Gibadullin; Sh. R. Zulkarneev; A. I. Gimazovа; V. A. Markelov; R. Kh. Zulkarneev; A. A. Bakirov; A. M. Avzaletdinov; N. Sh. Zagidullin (Креативная хирургия и онкология)
Introduction. Idiopathic pulmonary fibrosis (IPF) comprises an interstitial lung disease with unclear pathogenesis, rapid progression, and no effective treatment. Pulmonary fibrosis is reported to be one of the most severe complications induced by a new coronavirus infection COVID-19. The mechanisms triggering pulmonary fibrosis and leading to its rapid progression remain substantially unclear. Evidence suggests that immune and genetic factors contribute to the development of this disease. Among the latter, the role of long non-coding RNAs (dnRNAs) has been actively studied to date. Materials and methods. Considering the role of TP53TG1, LINC00342, H19, MALAT1, DNM3OS, and MEG3 dnRNAs as regulators of signaling pathways associated with fibroblast activation and epithelial-mesenchymal transition, the authors analyzed the expression level of selected dnRNAs in lung tissue and blood mononuclear cells of patients with IPF (N = 12), post-COVID-19 pulmonary fibrosis (N = 14), and in control group (N = 27). Results and discussion. Blood mononuclear cells in patients with IPF and post-COVID-19 PF revealed similar patterns of TP53TG1 and MALAT1 dnRNA expression. The level of relative expression of MALAT1 was significantly higher in patients with IPF (Fold Change=3.207, P = 0.0005) and with post-COVID-19 PF (Fold Change=9.854, P = 0.0003), while the relative expression level of TP53TG1 reduced in patients with IPF (Fold Change=0.4308, P = 0.0313) and with post-COVID-19 PF (Fold Change=0.1888, P = 0.0003 in blood mononuclear cells, Fold Change=0.1791, P = 0.0237 in lung tissue). Increased expression of DNM3OS in blood mononuclear cells (Fold Change=12.899, P = 0.0016) and lung tissue (Fold Change=9.527, P = 0.0001), LINC00342 (Fold Change=2.221, P = 0.0309) in blood mononuclear cells was revealed only in patients with IPF. Conclusion. Evaluation of the dnRNA expression profile of TP53TG1, LINC00342, MALAT1 and DNM3OS in blood mononuclei can be used as an informative and non-invasive biomarker in IPF and post COVID-19 PF.